2016
DOI: 10.1519/jsc.0000000000001211
|View full text |Cite
|
Sign up to set email alerts
|

Relative Intensity Influences the Degree of Correspondence of Jump Squats and Push Jerks to Countermovement Jumps

Abstract: The aim of this study was to determine the mechanical similarity between push jerk (PJ) and jump squat (JS) to countermovement jump (CMJ) and further understand the effect increasing external load may have on this relationship. Eight physically trained men (age 22 ± 3; height 176 ± 7 kg; weight 83 ± 8 kg) performed an unloaded CMJ followed by JS under a range of loads (10, 25, 35, and 50% 1RM back squat) and PJ (30, 50, 65, and 75% 1RM push jerk). A portable force platform and high-speed camera both collecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Cushion found that the greatest mechanical similarity with CMJ was observed at lower relative loads of the jerk and jump squat [19]. The mechanism behind is that subjects would alter the strategy in which they carry out the jumping and jerking as load increased such that the resemblance to CMJ characteristics is altered [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cushion found that the greatest mechanical similarity with CMJ was observed at lower relative loads of the jerk and jump squat [19]. The mechanism behind is that subjects would alter the strategy in which they carry out the jumping and jerking as load increased such that the resemblance to CMJ characteristics is altered [19].…”
Section: Discussionmentioning
confidence: 99%
“…The main finding was that jerk was more like a general training modality than specific in relation to jumping. However, Cushion et al [19] indicated that push jerk was more similar to countermovement jump (CMJ) than jump squat with the notion that jump squat is one of the commonly implemented exercises to strengthen jumping abilities. In contrast, other researchers, who also compared jerk, jump squat and CMJ, suggested that the loaded jump squat exercise was more related to jumping and sprinting abilities than to the push press [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, some studies have compared the similarities between WOPDs and specific sporting activities [ 87 , 95 , 111 113 ]. Cushion et al [ 111 ] compared the loaded push jerk and jump squat and a countermovement jump (CMJ). Unexpectedly, the push jerk was more related mechanically to the CMJ than the jump squat, which is one of the exercises commonly used to improve jumping abilities.…”
Section: Potential Benefits Of Weightlifting Overhead Pressing Derivamentioning
confidence: 99%
“…First, the use of WOPDs is a useful and well-supported strategy to improve weightlifting performance, due to the high number of failed attempts during the jerk phase in competition [ 97 , 98 , 105 ]. Second, WOPDs require the ability to develop force rapidly through the kinetic chain from the lower extremities to the upper extremities, which is mechanically similar to many sporting activities [ 55 , 70 , 111 ]. This movement pattern targets not only an impulsive triple extension of the ankles, knees and hips, but also optimizes motor control and coordination due to the key role of the trunk and lower body muscles in stabilising and transmitting forces in the closed kinetic chain [ 70 , 90 , 103 , 106 ].…”
Section: Conclusion and Practical Applicationsmentioning
confidence: 99%
“…Although two different exercises are being compared in these studies (push press and push jerk), the underlying message showed some similarities. Cushion et al (4) suggested that although load dependent, a greater mechanical similarity was observed between the push jerk and the CMJ (when compared to the jump squat exercise). Lake et al (11) proposed that the mechanical demand during the push press was comparable to the jump squat.…”
Section: Using the Push Press To Enhance Power Developmentmentioning
confidence: 99%